Short inter‐set rest blunts resistance exercise‐induced increases in myofibrillar protein synthesis and intracellular signalling in young males. Issue 7 (2nd June 2016) - McKendry, James; Pérez‐López, Alberto; McLeod, Michael; Luo, Dan; Dent, Jessica R.; Smeuninx, Benoit; Yu, Jinglei; Taylor, Angela E.; Philp, Andrew; Breen, Leigh
New Findings: What is the central question of this study? Does shorter rest between sets of resistance exercise promote a superior circulating hormonal and acute muscle anabolic response compared with longer rest periods? What is the main finding and its importance? We demonstrate that short rest (1 min) between sets of moderate‐intensity, high‐volume resistance exercise blunts the acute muscle anabolic response compared with a longer rest period (5 min), despite a superior circulating hormonal milieu. These data have important implications for the development of training regimens to maximize muscle hypertrophy. Manipulating the rest‐recovery interval between sets of resistance exercise may influence training‐induced muscle remodelling. The aim of this study was to determine the acute muscle anabolic response to resistance exercise performed with short or long inter‐set rest intervals. In a study with a parallel‐group design, 16 males completed four sets of bilateral leg‐press and knee‐extension exercise at 75% of one‐repetition maximum to momentary muscular failure, followed by ingestion of 25 g of whey protein. Resistance exercise sets were interspersed by 1 min ( n  = 8) or 5 min of passive rest ( n  = 8). Muscle biopsies were obtained at rest, 0, 4, 24 and 28 h postexercise during a primed continuous infusion ofl ‐[ ring ‐ 13 C6 ]phenylalanine to determine myofibrillar protein synthesis and intracellular signalling. We found that the rate of myofibrillar protein synthesis increased above resting values from 0 to 4 h postexercise with 1 (76%; P  = 0.047) and 5 min inter‐set rest (152%; P  < 0.001) and was significantly greater in the 5 min inter‐set rest group ( P  = 0.001). Myofibrillar protein synthesis rates at 24–28 h postexercise remained elevated above resting values ( P  < 0.05) and were indistinguishable between groups. Postexercise p70S6K Thr389 and rpS6 Ser240/244 phosphorylation were reduced with 1 compared with 5 min inter‐set rest, whereas phosphorylation of eEF2 Thr56, TSC2 Thr1462, AMPK Thr172 and REDD1 protein were greater for 1 compared with 5 min inter‐set rest. Serum testosterone was greater at 20–40 min postexercise and plasma lactate greater immediately postexercise for 1 versus 5 min inter‐set rest. Resistance exercise with short (1 min) inter‐set rest duration attenuated myofibrillar protein synthesis during the early postexercise recovery period compared with longer (5 min) rest duration, potentially through compromised activation of intracellular signalling. Abstract :